P036 B cell number reduction has a predictive value for response to belimumab in a cohort of patients with systemic lupus erythematosus. (March 2019) - Piantoni, S; Andreoli, L; Lowin, T; Kumar, R; Regola, F; Airò, P; Cavazzana, I; Franceschini, F; Tincani, A; Pongratz, G
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: Belimumab, the anti-B-cell activation factor (BAFF) agent, is approved for the treatment of refractory systemic lupus erythematosus (SLE). Its effect on the number of circulating B-cells is selective on naïve (CD19+CD27-IgD+) and immature transitional B-cells (CD19+38high24high) whose survival is strictly BAFF-dependent. On the opposite, CD27+ memory B-cells are preserved during belimumab therapy, being their maturation more related to the activation of B-cell receptor pathways. Objectives: The aim of this study is the evaluation of B-cell subpopulations in a cohort of SLE patients treated with belimumab. Methods: Phenotypic analysis of peripheral blood B-lymphocytes was made by flow-cytometry in a cohort of SLE patients treated with belimumab. SLE-disease activity was assessed by SLEDAI-2K score. BAFF was tested by ELISA. SPSS was used for statistical analysis. Results: The relative change of BAFF levels at 6 and 12 months from baseline showed linear correlation with the percentage of naïve B-cells (Pearson correlation=0.645, p=0.044 and 0.639, p=0.002, respectively) and of transitional B-cells (Pearson correlation=0.768, p=0.009 and 0.623, p=0.055, respectively). The percentage and absolute number of naïve B-cells showed a progressive decrease during time (ANOVA, p=0.013 and p=0.001 respectively). In terms of response prediction, a significant association of SLEDAI percentage improvement at 12 months with the decrease of total number of B-cells within the first 6 months of therapy was observed (Log regression r=0.707, p=0.05). Conclusions: BAFF inhibition induces B-cell number modifications in a SLE cohort. The reduction of total number of B-cells within the first six months shows predictive value for SLEDAI response after the first year of therapy. References: Vossenkämper A, Lutalo PM, Spencer J. Translational mini-review series on B cell subsets in disease. Transitional B cells in systemic lupus erythematosus and Sjögren's syndrome: clinical implications and effects of B cell-targeted therapies. Clin Exp Immunol 2011;167(1):7–14. Boneparth A, Davidson A. B-cell activating factor targeted therapy and lupus. Arthritis Res Ther 2012;14(Suppl 4):S2. Jacobi AM, Huang W, Wang T, Freimuth W, Sanz I, Furie R, et al. Effect of long-term belimumab treatment on B cells in systemic lupus erythematosus. Arthritis Rheum2010;62:201–210. Acknowledgements: The authors are grateful to Carla Bosio and Alessandra Paletti, laboratory technicians at the Laboratory of Rheumatology and Clinical Immunology in Brescia, for their valuable collaboration. The authors wish to thank the nurses of the Rheumatology and Clinical Immunology Unit in Brescia for their support in blood collection. Disclosure of Interest: None declared.